Stable housing, ‘home’ and desistance: Views from Aotearoa New Zealand - Low, Grace (Criminology & criminal justice, 2025)
There has been little theoretical development concerning the role of housing and the more subjective notion of ‘home’ in supporting desistance from crime. Through narrative interviews with 16 men with histories of imprisonment in Aotearoa New Zealand, this article explores key psycho-social benefits of home that support men to desist from crime. The article expands knowledge on the role of place and space in desistance by emphasising that to fully engage with the desistance process, those leaving prison need more than a roof over their heads; they need a home with psycho-social benefits that enhance their sense of wellbeing and ontological security. It is argued that a home provides a crucial setting for those leaving prison to ‘do’ desistance, and it is imperative that reintegration policy and practice recognise the psycho-social benefits of home.